An Efficient Hybrid Model in Analyzing Nonlinearly Loaded Dipole Antenna above Lossy Ground in the Frequency Domain - Ostadzadeh, S. R. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a hybrid model is proposed for including lossy ground effect on scattering response from nonlinearly loaded dipole antenna. In this model, at first the input admittance and induced current at dipole antenna situated over lossy ground are efficiently modeled based on the fuzzy inference concepts. Volterra series model is then applied to compute the induced voltage across nonlinear load at different frequency harmonics. Numerical examples show not only the accuracy of the proposed hybrid model but also a high computational efficiency in comparison with previous hybrid models.